Hannah Arendt and the uses of history : imperialism, nation, race, and genocide - King, Richard H.; Stone, Dan, 1971- (Berghahn Books, 2008)
Hannah Arendt first argued the continuities between the age of European imperialism and the age of fascism in Europe in 'The Origins of Totalitarianism'. This text uses Arendt's insights as a starting point for further investigations into the ways in which race, imperialism, slavery and genocide are linked.